Low‐Profile Wideband Metasurface Antenna With Polarization Reconfiguration via Resistor Control and Reduced RCS for Enhanced Wireless Communication - Ding, Zhendong; Li, Jiawang; Zhang, Dan; Chia, Michael Yan‐Wah; Wang, Hao; Nasimuddin, Nasimuddin (International journal of circuit theory and applications, 2025)
ABSTRACT This paper presents a low‐profile, single‐layer, broadband, polarization‐reconfigurable metasurface antenna with a low radar cross section (RCS). The design leverages characteristic mode analysis (CMA) applied to a staggered elliptical‐shaped unit cell metasurface. The unique arrangement of the elliptical‐shaped elements, oriented at 90°, promotes mode fusion through CMA, effectively reducing RCS. Additionally, the analysis of a defective floor with branching reveals a critical characteristic angle (CA) of 90°, essential for generating circular polarization (CP) waves. Experimental measurements indicate that the antenna prototype achieves a −10 dB impedance bandwidth (IBW) from 5.5 to 8.3 GHz (40.6%), a 3‐dB axial ratio bandwidth (ARBW) from 6.3 to 8.2 GHz (26.2%) and a peak gain of 5.1 dBi at 6.3 GHz. By integrating resistors, the antenna supports switching between CP and linear polarization (LP), as well as across different frequency bands, resulting in three distinct operating states (with IBWs of 26.5%, 26.9%, and 26.9%, respectively). Additionally, the metasurface structure achieves a notable reduction in monostatic RCS across the frequency range from 2.0 to 22.0 GHz, resulting in a substantial 166.7% reduction and a 6 dBsm decrease in RCS within the IBW of 6.3 to 7.2 GHz. The exploded view of low‐profile low‐RCS wideband metasurface antenna with polarization reconfigurable. A low‐profile, single‐layer, broadband, polarization‐reconfigurable metasurface antenna with RCS is proposed. CMA of a defective floor with branching reveals a critical CA of 90°, essential for generating CP waves. Resistance is used to switch between circular polarization and linear polarization to achieve polarization reconfiguration.